Enhancing Authentic Leadership PsyCAP, Job Stress and Job Satisfaction: Innovating Combined Effect - Sultana, Umme Salma; Mohd Ridzuan, Darun; Liu, Yao; Andalib, Tarnima Warda (Future Academy, 2018)
The purpose of this paper is to review the relationship of authentic leadership, psychological capital or PsyCap, job satisfaction, and job stress. The job satisfaction has great importance in any organization because employees who are highly stressed in their workplace may not be satisfied. Many kinds of research already tried to develop authentic leadership and psychological capital, researchers also attempted to find out different job outcomes by practicing authentic leadership and PsyCap. A number of previous studies reviewed to understand the relationship between job stress and job satisfaction, and how job stress affects job satisfaction. Each component of authentic leadership and psychological capital will be supportive of increasing leaders and employee's job satisfaction. The components of authentic leadership and psychological capitals are described in a manner that assists to prove its ability to minimize job stress and achieve job satisfaction. Observing from the previous literature present paper proposing that authentic leadership and psychological capital together could be one of the solutions to decrease job stress and increase job satisfaction. Furthermore, this study put together previous studies, which supports the proposed solution and concludes by discussing the reasons behind this proposed solution.